THE JURISDICTION OF ESSENTIALS: THE LIMIT OF THE STRUCTURING PROCESS AND THE COUNTERMAJORITARY DUTY IN THE BRAZILIAN DEMOCRATIC STATE (CIPEEX, 2026)
This summary defends the structuring process as a legitimate and necessary tool of the judiciary's counter-majoritarian function. In a scenario of systemic rights violations and complex environmental disasters, judicial intervention to reorganize public policies is routinely attacked under the heading of judicial activism. In opposition to this criticism, it is argued that, in the face of the paralysis of political powers—which respond to majority logic and short-term economic interests—the structuring process becomes an indispensable instrument for safeguarding constitutional mandates related to environmental crises. Based on the theory of counter-majoritarian difficulty, it is demonstrated that this action does not represent usurpation, but rather the fulfillment of the duty to protect the ecological minimum and the rights of vulnerable groups, such as victims of environmental racism. It is thus concluded that the structuring process is not an anomaly, but rather the appropriate judicial response to a chronic failure of representative democracy.
Keywords: Processo Estruturante; Dificuldade Contramajoritária; Ativismo judicial